IMPLEMENTASI HAK WARIS PEREMPUAN KE DALAM AWIG-AWIG DESA PAKRAMAN - Ida Ayu Sadnyini (University of Udayana, 2016)
Women in Bali Customary Law have not received legal heir protection. This is because the Hindu community in Bali embraces patrilineal kinship system. In the development of the Assembly Pakraman (MDP) Bali Number III of 2010, they have taken the initiative to give women the right to inherit the extent of the joint property of her parents. As the MDP decree has not been implemented into awig awig Pakraman, women are still in the same position. This condition causes the researcher to study the